Design of a pneumatic launcher and glider - Pang, Shiuh Woon. (2009)
This project aims to design a reusable glider and its pneumatic launcher. The glider is to be activated by compressed air energy, thru the launcher. The size of this glider is about 150mm for the wing span and 200mm for the fuselage. The whole system of this design was based on the pneumatic power and the aerodynamics of a fixed wing. Some patent research on the existing inventions had been carried out. This project report discusses the design process, a simple testing, design principles, simple calculations, and the detail designs of the glider and launcher. Measurement of the horizontal displacement, flight time, and its accuracy were performed, by adjusting the angle of incidence. The material of the glider is selected. Hence, the weight of the glider is kept below 300gm.